ICRT 2021 - Zhai, Wanming; Wang, Kelvin C. P.; Zhu, Shengyang (American Society of Civil Engineers, 2022)
Proceedings of the Second International Conference on Rail Transportation, held in Chengdu, Sichuan Province, China, July 5-6, 2021. Sponsored by Southwest Jiaotong University and the Transportation & Development Institute of ASCE.This collection contains 59 peer-reviewed papers on recent rail industry research, including high-speed railways, heavy-haul railways, and urban rail transit systems.Topics include: infrastructure development; design, construction, and maintenance; rail vehicles; communications systems; traction power; and operations and the environment.This proceedings will be of interest to practicing engineers and researchers working in all areas of rail transportation.
Keywords: elektronické knihy; electronic books